MODEL OF DEVELOPMENT OF QUALITY OF HIGHER EDUCATION SERVICES IN IMPROVING STUDENT SATISFACTION (STUDY AT MUHAMMADIYAH UNIVERSITY MALANG) - Sri Nastiti Andharini; Marsudi Marsudi; Nurjannah Dewi (Manajemen Bisnis, 2020)
The initial research that has been conducted aims to know the quality of college education services and know the possible quality of college education services to improve student satisfaction. In further research that has been conducted aims to determine the concept model of development of quality education services to improve student satisfaction, and create operational standards procedures (SOP) quality services education services that can be done to improve student satisfaction. In the initial study, the data collection technique used was questionnaire distributed to 255 respondents, with purposive sampling. The criteria used are active students, at least semester 3 in the Management Study Program. For further research is used focus discussion group to key person, namely faculty leaders and study programs, using quota sampling. Based on the results of the scale range obtained results, reliability, responsiveness, assurance, empathy, and physical evidence in the category of good. Based on the results of logit regression: simultaneously the dimension of service quality affects student satisfaction, while partially affecting student satisfaction is the conformity of curriculum and materials taught to the needs of students, assignments provided useful, academic supervisors have adequate competence, the existence of unit / insurance for students, care and special daily from lecturers / instructors to students who have academic difficulties, academic supervisors open consulting services for students, neatness and sympathetic lecturers / instructors, and academic officers. Based on the results of discussions with key persons, to improve student satisfaction, need to be improved and developed marketing mix of services through the resulting services, process, distribution, people, physical facilities.